ANALISIS RASIO DALAM PENERAPAN CASH TEMPO DIDALAM NERACA PERUSAHAAN DI MASA PANDEMI COVID 19 DI PT PILAR PITOE SEJAHTERA KEDIRI - Wulandari; Sary, Clara Devy Yulvia Ratna; Rohma, Miptaqul (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2023)
The purpose of this study was to determine the effect of the application of Cash Tempo in the balance of the Balance Sheet and the application of Cash Tempo for operational continuity during the Covid Pandemic - 19 at PT Pilar Pitoe Sejahtera Kediri. Based on the discussion of the results of the research conducted, it can be concluded that the application of cash tempo has a role in the company's balance sheet. The results of the research PT Pilar Pitoe Sejahtera has implemented the cash tempo method well, this is evidenced by the company's activities in maintaining its obligations to third parties are well maintained, providing information to users and third parties on the application of Cash Tempo, and the company's operations continue to run normally. Based on the conclusions that have been stated by the author, the author tries to provide some suggestions that might be useful for the company, among others: a better document filling system, so that the data for balance sheet reporting is more current, maintaining approaching the obligated parties more intensely, and continuing to reminder regularly to parties who have obligations.